2005
DOI: 10.1596/1813-9450-3761
|View full text |Cite
|
Sign up to set email alerts
|

Is Skill-Biased Technological Change Here Yet ? Evidence From Indian Manufacturing In The 1990

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 19 publications
4
44
0
3
Order By: Relevance
“…Hur, Seo, and Lee (2005) showed that information and communications technology diffusion in Korean industrial sectors was positively correlated with skill upgrading over the 19961999 period. Berman, Somanathan, and Tan (2005) found evidence of skill-biased technological change in India in the 1990s using panel data disaggregated by industry and state. Bustos (2011) found that skill upgrading within firms increased relative demand of skilled labor in Argentina.…”
Section: Introductionmentioning
confidence: 98%
“…Hur, Seo, and Lee (2005) showed that information and communications technology diffusion in Korean industrial sectors was positively correlated with skill upgrading over the 19961999 period. Berman, Somanathan, and Tan (2005) found evidence of skill-biased technological change in India in the 1990s using panel data disaggregated by industry and state. Bustos (2011) found that skill upgrading within firms increased relative demand of skilled labor in Argentina.…”
Section: Introductionmentioning
confidence: 98%
“…Studies using firm-level data of developing countries, albeit limited in number, have confirmed that the level of trade and openness to foreign technology is related to higher share of skilled workers (Lee and Wie 2015a, Almeida 2010, Berman et al 2005. For instance, using firm-level data from East Asian developing countries, Almeida (2010) showed that higher levels of technological innovation and foreign direct investment (FDI) are related to greater skill demand.…”
Section: Technology Change and Skill Demand By Enterprises In Asiamentioning
confidence: 99%
“…In the 1990s, the greater demand for skilled workers was mostly due to the increasing level of technology in each industry, as well as the increase in output and capital-skill complementarity, combined with rapid capital investment from India (Berman et al 2005). Studies have confirmed that the increasing returns to skills, especially of males, due to skill-biased technological changes within industries were the driving force behind the increasing income disparity across skills and between gender in the country (Mehta and Hasan 2012, Kijima 2006, Chamarbagwala 2006.…”
mentioning
confidence: 99%
“…Moreover, the authors highlight that SBTC provides no insights on a set of related issues such as the gender-wage gap. Also a recent study by Berman et al (2005) on India's manufacturing sector devised for the period of 1983 to 1998 revealed inconclusive results regarding SBTC.…”
Section: Empirical Literature Review On the Skill Premiamentioning
confidence: 99%